Revitalisasi Peran Mahasiswa Menjaga Kelestarian Hidup dengan Falsafah Hidup Poda Na Lima - Hasan Basri Lubis; Muhammad Nuddin (Marpokat: Jurnal Pengabdian Kepada Masyarakat, 2023)
In the era of globalization, environmental problems are growing rapidly, meaning that these problems are a serious threat to the nation and state. High population numbers are one of the main triggers for the destruction of existing environmental sustainability, followed by a decline in attitudes to protect the environment. Garbage accumulation at Sipirok Market is very common due to the unavailability of adequate facilities so that people can burn garbage and dispose of it somewhere. This study aims to describe environmental sustainability in the Tabagsel area and provide solutions to students regarding their functions and roles. The research method used in this research is descriptive research. The results of this study are that students will be able to protect the environment and preserve nature by upholding the philosophy of Poda Na Lima. The philosophy of Poda Na Lima is the basis of teachings, education, advice and community rules which are a way of life.